2000
DOI: 10.1002/1097-4644(20000915)78:4<650::aid-jcb14>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Protein-protein interactions that precede the nuclear entry of goat uterine estrogen receptor under cell-free conditions

Abstract: Mechanisms associated with a regulated nuclear entry of the goat uterine estrogen receptor (gER), under the influence of estradiol, have been examined using a cell-free system. The gER transport into the nucleus is mediated by a 55-kDa cytosolic protein, p55. Experimental evidence has been provided to demonstrate that p55 binds to the nuclear localization signals (NLS) on the gER. Under hormone-free conditions, a 28-kDa protein, p28, binds to the NLS and prevents the p55 interaction with the NLS. This inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2001
2001
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Several members of the Hsp family, including Hsp70, also have the capacity to bind to nuclear receptors, such as estrogen receptor alpha (Smith and Toft 1993). Hsps have been linked to the intracellular transport of steroid receptors (De Franco et al 1997;Sai Padma et al 2000) and can influence receptor-DNA interactions (Landel et al 1997). Recent work by Hurd et al (2000) found that transient transfection of Hsp70 produced a 2-to 3-fold increase in estrogen-stimulated estrogen response element-luciferase reporter activity in MCF-7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several members of the Hsp family, including Hsp70, also have the capacity to bind to nuclear receptors, such as estrogen receptor alpha (Smith and Toft 1993). Hsps have been linked to the intracellular transport of steroid receptors (De Franco et al 1997;Sai Padma et al 2000) and can influence receptor-DNA interactions (Landel et al 1997). Recent work by Hurd et al (2000) found that transient transfection of Hsp70 produced a 2-to 3-fold increase in estrogen-stimulated estrogen response element-luciferase reporter activity in MCF-7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Studies carried out in our laboratory on the nuclear transport of goat uterine estrogen receptor α has clearly identified the involvement of two proteins: a 55 kDa protein (p55) that binds to the NLS on the ER and a 12 kDa protein (p12) that recognizes p55 on the one hand and a NPC protein on the other [Nirmala and Thampan, 1995; Sai Padma and Thampan, 2000; Sai Padma et al, 2000]. In the alternative estrogen receptor system that involves the naER, the NLS binding protein that mediates the transport of naER to the nucleus is a 58 kDa protein, p58.…”
mentioning
confidence: 99%